2017
DOI: 10.1002/jso.24619
|View full text |Cite
|
Sign up to set email alerts
|

ITADE flap after mastectomy for locally advanced breast cancer: A good choice for mid‐sized defects of the chest wall, based on a systematic review of thoracoabdominal flaps

Abstract: ITADE allows extensive coverage areas, an early start of adjuvant treatment and it can be performed without requiring a reconstructive team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…We would like to make a clarification regarding the systematic review previously reported in your journal . The author of one of the articles raised a question about the fact that I did not consider their flap to be a fasciocutaneous flap but rather a dermofat flap.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We would like to make a clarification regarding the systematic review previously reported in your journal . The author of one of the articles raised a question about the fact that I did not consider their flap to be a fasciocutaneous flap but rather a dermofat flap.…”
mentioning
confidence: 99%
“…In the presence of a subcutaneous pedicle, the tissue flap can be considered a Type A fasciocutaneous flap . Evaluating the published article and using the above classifications, I reviewed all the considered dermofat flaps described in ITADE’s article . Baroudi et al (1978) “reported that the “dissection is done at the level of the aponeurosis, from the end back to the base of the flap.” Tai et al (1974) reported that “it is wise to leave the deep fascia under the flap.” The flap described by Das and Choudhury (2013) was described using skin and subcutaneous tissue.…”
mentioning
confidence: 99%
See 3 more Smart Citations